Fermentation kinetics and ruminal degradability in vitro of diets with different nitrogen source - Aguirre Valverde, Carlos (2017)
The objective of this work was to determine the fermentation kinetics and in vitro ruminal degradability of diets with different nitrogen source for feeding ruminants. Three diets were formulated (D) with different sources of nitrogen D1 (fishmeal), D2 (soybean paste) and D3 (urea), these were iso-caloric with 2900 kilocalories of digestible energy in dry matter (kcal ED / MS ) and iso-proteins 13% crude protein (PB). The incubation periods used were 0, 2, 4, 8, 12, 24, 48 and 72 hours. In the evolution of the Ph in the ruminal kinetics of the three diets with different sources of nitrogens, it can be determined that the D3 and D1 recorded the highest pH (P